Application of trusted computing in internet voting - Mohd. Zulkifli, Mohd. Zaid Waqiyuddin (2009)
Over the years, improvements in technology and security, along with our increasing comfort with the Internet, have seen many applications and services being delivered online. Despite this, the adoption of Internet voting has been remarkably slow, mainly due to the unique requirements of elections, its scale and the disastrous consequences of failure. In the academic world however, many interesting techniques and protocols have been discovered that could help improving the security and robustness of Internet voting. Unfortunately, most of the designs often make very demanding assumptions or otherwise, are very limited in their effectiveness. This paper looks at Trusted Computing technology as a means to satisfy some of the assumptions, and to see its effects in improving the overall security of Internet voting architecture. This paper also looks at the possibility of Trusted Computing making certain Internet voting technologies unnecessary or redundant.